(untitled) (Environment & Health, 2023)
The purpose of the current study is to systematize the established causative factors of cancer based on the analysis of literary and scientific sources that highlight epidemiological findings about the influence of environmental factors on the incidence of malignant neoplasms. Research materials and methods: bibliosematic, bibliographic, hygienic, data from own research and materials from literary sources. The results. By systematizing the established causative factors of cancer based on the analysis of literary data and scientific observations in the historical aspect, the main epidemiological findings regarding the influence of environmental factors on the incidence of malignant neoplasms were determined. Special emphasis is placed on the problem of tobacco smoking. The criterion scale of the role of individual factors of the environment, production, natural and household factors to the social conditions of life in the development of cancer pathology is given. The role of epidemiological researches in the study of malignant neoplasms and the identification of causal factors is illustrated by the materials of observations of thyroid cancer in a number of regions of Ukraine 30 years after the accident at the Chernobyl nuclear power plant. Conclusion: Epidemiological research of malignant tumors is a promising scientific direction and, above all, in the process of studying the role of environmental pollution, climatic, geographical, professional and other factors of human life and needs wider use within Ukraine.